A 3D Convex Hull algorithm for modelling medical data in a virtual environment. (6th May 2008) - Yaacoub, Fadi; Hamam, Yskandar; Abche, Antoine
Computer-based surgical simulation systems are one of the most recent technologies in Virtual Reality (VR). These intelligent systems have become the training method and the tool to acquire valuable information for many medical students. They allow the students to interact with the anatomical structures by modelling and displaying virtual objects on the computer screen. Since a real object does not have a deterministic shape, it is impossible to derive a geometric equation for modelling purposes. Thus, alternative approaches are based on Convex Hull (CH) algorithms to construct the convex envelope of any object and to simulate a realistic environment with exact Collision Detection (CD) between objects during the training on a surgical operation. In this paper, a hybrid approach to generate the CH is developed and presented. The new algorithm is validated by performing a comparison with three conventional methods, namely, the Gift Wrapping, the QuickHull and the Chan algorithm. The evaluation is achieved by generating the convex envelopes of 3D wrist and knee bones. The results show the improvement associated with the proposed approach.